Gene and chromosome analysis. Part A - Adolph, Kenneth W (Academic Press, 1993)
This volume details experimental protocols including, gene cloning, cell hybrids, chromosome mapping, and gene expression.
Methods in molecular genetics ; Vol. 1
Keywords: Chromosome Mapping; geny; genetika, lékařská genetika; Genes; Molecular Biology; embryologie a teratologie; mapování chromozomů; molekulární biologie